5,6,4'-Trihydroxy-7,8,3'-Trimethoxy Flavone-4'-O-β-D-Xylopyranosyl-(1→2)-O-α-L-rhamnopyranoside: A Novel Bioactive Flavone Glycoside from the Mucuna prurita Hook - Yadava, R.N.; Jain, Shivani (Asian Journal of Chemistry, 2010)
A novel flavone glycoside isolated from the seeds of Mucuna prurita and its structure was identified as 5 ,6,4'-trihydroxy-7 , 8, 3'-trimethoxy flavone-4' -O-β-D-xylopyranosyl-( 1→2)-O-α-L-rhamno-pyranoside by various chemical degradations and spectral analysis. This compound showed antimicrobial and antifungal activity against. various gram +ve gram -ve bacteria and fungi.